THE USE OF VIDEOS IN TEACHING VOCABULARY IN AN ELEMENTARY SCHOOL : A Quasi Experimental Study of Fourth Grade Students at One School in Bandung - Lestari Kaosar, - (2011)
This research investigated whether the use of videos improving students'vocabulay. Video was chosen because it provides audio-visual media in one package to facilitate the students to learn vocabulary. The study employed a Quasi-experimental design in one Elementary School in Bandung. Two classes, each of which consists of 36 students, was selected to be the samples of this research, one class as the control group and one class as the experimental group. The treatment was given in six sessions and multiple choice test was used as the research instrument on pre and post-test. Then, the data were obtained through a pre-test, post-test and questionnaire. The data gathered through pre-test and post-test computed one by one using IBM SPSS Statistics 16.0 for Windows while data from questionnaire were analyzed based on the frequency students' answers and then were calculated and interpreted into percentages. The result of the study showed that the experimental group had better vocabulary mastery. The statistical computation showed that video effective in improving students' vocabulary mastery (tobt 3.987>tcrit 1.994), r= 0.80). Moreover, the data from questionnaire showed that the videos positively responded by the students.